Nutritional profile of elementary school students in nine municipalities of a state from the northeast of Brazil (Research, Society and Development, 2020)
The aim of this research was to evaluate the anthropometric profile of elementar school students between 3 and 15 years of age in Schools of the Social Service of Commerce (SESC) in 09 municipalities in the state of Piauí and to describe the profile of their nutritional status according to age and sex. This is a cross-sectional, descriptive and census survey, carried out in the second semester of 2019. The sample was composed of a total of 1261 students of both sexes, being 52.1% male and 47.95% female. The project was approved by the Research Ethics Committee of the Hospital Universitário Antônio Pedro of Universidade Federal Fluminense. Of the total, 18.20% were less than 5 years old and 81.80% were between 5 and 15 years old. It was observed that children up to 5 years old, 3.93% were obese, 17.47% were overweight, 3.93% were thin and 4.37% were markedly thin. As for schoolchildren over 5 years of age, there was a prevalence of 3.88% for cases of severe obesity, 10.95% for cases of obesity, and 15.50% for cases of overweight. The cases of thinness corresponded to 3.00%, and 2.81% for cases of marked thinness. It was concluded that the rates of overweight and obesity were high, as well as the presence of malnutrition, indicating the need for specific interventions aimed at the recovery and maintenance of adequate nutritional status so that future chronic diseases are prevented and the health of children and adolescents is preserved.